การมีส่วนร่วมของชุมชนในการอนุรักษ์และใช้ประโยชน์จากยางนา/Local Community Participation in Yang Na Conservation and Utilization - แสงอาวุธ วรวีร์; สมสวัสดิ์ จินตนา; จิรสัทธรรม นรชิต (Journal of Humanities and Social Sciences (HUSOKKU), 2019)
This research project aims to explore incentive factors for farmers in applying the benefits of Dipterocapus Alatus, known as Yang Na, in the rural community by using participatory action research approach. The study area is Na Nong Toom sub-district, Chum Phare district, Khon Kaen Province. In this study, the process of Appreciation-Influence-Control (A-I-C) was utilized to extract information beyond on socio-economic data of surrounding rural villages. AIC helps researchers to get involved with the community through planning reflection for building adaptive capacity. We investigate the villagers’ attitudes toward Yang Na’s benefits and the product innovation created by scientific research. The demonstration of Yang Na products technology was conducted to observe farmer’s reaction including resin filtration, making soup using the main ingredients of Yang Na (e.g., leaves or resin). The results show that farmers responded positively to Yang Na productions and tended to profoundly engage in managing Yang Na forest in both private land and community forest. Furthermore, we found that the participatory action research shed light on two motivations causing such an engagement in this community. Firstly, villagers were motivated by Yang Na as a new alternative source to rise their income. Secondly, the accurate knowledge about regulations of Yang Na given to the villagers encouraged them to change perception and have positive attitude to utilize the benefits of Yang Na. We also found that research participants are enthusiastic to engage in establishing a project and plan to set up a community group, named “Yang Na Aura Na Nong Thum Soap,” within six months. The result of this study suggests two issues. First, the initiative project of Yang Na soap should be further supported continually. Moreover, the ongoing process can provide more knowledge for broader vision such as production, marketing, product distribution, and leadership in the community. The second point is involving in a copyright issue of producing Yang Na soap, and it is an urgent issue. Khon Kaen University can initiate the collaboration among local administration, agency, and community to successfully pass the barrier of ownership. Such an achievement can provide an opportunity to further develop a product as a new identity for a community. It is possible that the product is one of the One Tambon One Product (OTOP) in the future.